Transforming HR Management: Exploring The Benefits of Tools For HR Analytics in The Pharmaceutical Industry - Nelson, Alden; Christiani, Gladys; Sembiring, Tesalonika; Lie, Wynne; Saputra, Eric Gilbert; Hamdatudin, R. Abdulloh (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This study explores the transformative impact of Human Resource (HR) analytics tools within the pharmaceutical industry, focusing on their capacity to optimize HR processes, enhance decision-making, and improve workforce management. In an industry characterized by high demand for data-driven insights, HR analytics tools serve a critical role in identifying patterns and trends, assessing employee performance, and formulating strategic HR decisions. The research underscores the integration of digital tools like HR Information Systems (HRIS), data visualization software, and Artificial Intelligence (AI)-driven analytics. These technologies provide valuable insights that help pharmaceutical companies to align their HR strategies with organizational goals, improve productivity, and foster employee engagement. By delving into the structure, processes, and outcomes associated with HR analytics, this study sheds light on the importance of these tools in driving the HR transformation necessary to sustain competitive advantage in a rapidly evolving market.